The prevalence, risk factors and lifestyle patterns of Jordanian females with premenstrual syndrome: a cross-sectional study - Mera A Ababneh; Malak Alkhalil; Abeer Rababa'h (Future Science OA, 2023)
Aim: The study aims to assess factors associated with premenstrual syndrome (PMS) and the frequency of using painkillers to relieve premenstrual pain. Methods: This is a cross-sectional study of 1580 premenopausal women. An online self-administered questionnaire consists of sociodemographics, and the diagnostic criteria using the Arabic Premenstrual Syndrome Scale (A-PMS). Results: The prevalence of PMS among Jordanian females was 94%. Moreover, a significant correlation was found between several factors, including BMI, family history of PMS, smoking, and herbal tea consumption and the psychological, physical and behavioral symptoms of PMS. Furthermore, analgesic use for pain relief and food cravings were significantly associated with psychological, physical and behavioral PMS symptoms. Conclusion: PMS is highly prevalent and affects women in different life aspects.